O setor elétrico brasileiro: formação, matriz energética e estrutura tarifária - Guimarães, Daniel Jorge Teixeira (2013)
The electric power industry has a key role in economic growth and development of a nation. Electricity is a basic input to the productive sector, its cost plays an important weight on the competitiveness of domestic industry. This study aimed to make a historical-structural analyses of the Brazilian electric power industry, aiming to examine the roles of the private and public sectors in the development of the industry. Furthermore, analyzes of the Brazilian energy matrix and its influence on current energy tariff. To that end, was conducted literature relevant to the topic and international comparison. This study found that for the continued growth of the supply of electricity is extremely important the role of a central long-term planner agent, role of the state, along with the active participation of the private sector in the form of investments and efficiency gains in the industry. Also check the reasons for the high value of the Brazilian electricity tariff, given the low cost of the predominant energy source in its energy matrix, and indicates alternatives for its reduction.